APLIKASI WEB UNTUK SISTEM INFORMASI AKADEMIK SMA NEGERI 33 JAKARTA - Hidayatun, Nunung; Herlawati, Herlawati; Frieyadie, Frieyadie (LPPM Universitas Nusa Mandiri, 2013)
Educational Information System up to now is off line information system generally, where information is only be created manually which are through official documents that are stored, print media and bulletin board on school’s wall. Based on the explanation above, then be increased services in the field of information. Manual information system becomes a digital information system (computerize) in the form of online website. On this online website, it’s used PHP script and MySQL database. The purpose of this planning system is facilitating in delivery of educational information widely, it’s not only for the teachers and students but also accessible for the public on the internet. Through thisdevelopment system, access information can be done whenever and wherever without directly related with existing resources.